Dual Monetary Policy and Inflation Dynamics in Indonesia - Maharani, Alyana; Hapsari, Meri Indri (Jurnal Ekonomi Syariah Teori dan Terapan, 2024)
This study aims to provide information about dual monetary policy on inflation in Indonesia in 2019-2023. This study uses a quantitative approach with VECM analysis technique. The results show that in conventional monetary policy, conventional bank lending has a significant effect in the short and long term, while SUN yields only have an impact in the long term. On the other hand, Islamic monetary policy shows that SBIS yields and Islamic bank financing have a significant effect in the long and short term. IRF analysis shows that conventional monetary policy can stabilize inflation in the fifth period, while Islamic monetary policy in the second period. Overall, Islamic monetary policy is more effective that conventional monetary policy in stabilizing inflation in Indonesia in 2019-2023.